(Invited) Epitaxy of GaN on Si (111) for Power Electronics, RF and LEDs. (20th July 2018) - Charles, Matthew; Kanyandekwe, Joël; Bos, Sandra; Baines, Yannick; Morvan, Erwan; Torres, Alphonse; Templier, François; Plissonnier, Marc
Abstract : The semiconductor industry has a highly developed infrastructure for silicon processing with a high level of automation, state of the art facilities and the ability to deal with large volumes which lead to lower fabrication costs. GaN on silicon can take advantage of this maturity of process, especially with the use of 200 mm substrates giving access to large CMOS compatible fabs. This requires specific growth tools with excellent uniformity and low defectivity to ensure compatibility with these processing lines. Combining the industrialization techniques of silicon with the outstanding properties of a wideband gap material such as GaN results in high performance devices and new functionality for a wide variety of applications in power conversion, radio-frequency electronics and opto-electronics. All three of these applications are becoming increasingly present in the global semiconductor market.